Learning C♯ 3.0 - Liberty, Jesse (O'Reilly Media, 2008)
If you're new to C♯, Learning C♯ 3.0 is the ideal way to get started. Learning C♯ 3.0 starts with the fundamentals and takes you through intermediate and advanced C♯ features-including generics, interfaces, delegates, lambda expressions, and LINQ. You'll also learn how to build Windows applications and handle data with C♯. Each chapter offers a self-contained lesson with plenty of annotated examples, illustrations, and a concise summary. No previous programming experience is required.